Intervention transnationale et moralisation de la gestion de la propriété en milieu rural au Maroc - Turner, Bertram (Anthropologica, 2022)
This article explores transformations of property relations within the framework of the integration of rural areas with processes of neo-liberal globalization. The way that interconnections among various scales reconfigure property relations in rural environments is analyzed. In certain circumstances, these changes involve a rearrangement of the space for manoeuvre of various actors based on religious and moral discourses which bind rural areas to their global environment. The article highlights the socio-juridical conditions under which popular religious identity provides a frame of reference for appropriate local management of rural property vis-a-vis a global standardization of property relations. The empirical data presented come from the Souss region of southwest Morocco.